Microlearning in the Digital Era: Educational Technology Strategies for a Generation with Short Attention Spans - Mokhamad Yaurizqika Hadi (EduTech Journal, 2026)
The shortening of human attention spans in the digital age—particularly among Generation Z and Generation Alpha—presents significant challenges to traditional instructional models that rely on extended, sustained engagement. Microlearning, defined as the delivery of educational content in short, focused, and modular units, has emerged as a strategically aligned response to this cognitive reality. This study conducts a systematic literature review of 20 peer-reviewed publications from 2021 to 2024, examining the theoretical foundations, practical implementations, technological enablers, and measurable outcomes of microlearning in digital educational contexts. Findings indicate that microlearning consistently improves knowledge retention, learner motivation, and self-directed learning when designed according to cognitive load theory and spaced repetition principles. Digital platforms—including TikTok, mobile LMS applications, AI-powered chatbots, and gamified environments—serve as effective delivery mechanisms for microlearning content. However, challenges including fragmentation of deep learning, over-reliance on passive consumption, and assessment validity require careful pedagogical consideration. The study concludes with a proposed framework for effective microlearning design in digital educational technology contexts.